Pyelo-ureteral junction obstruction in poorly functioning kidneys: Does conservative management play a role in pediatric patients? - Zarfati, Angelo; Mele, Ermelinda; Villani, Maria Felicia; Capozza, Nicola; Castagnetti, Marco (Frontiers in Pediatrics, 2023)
Abstract: Background: management of Pyelo-ureteral Junction Obstruction (PUJO) in poorly functioning kidneys in pediatric patients is still controversial, particularly regarding the role of conservative treatment. Aim: to compare outcomes in pediatric patients with PUJO in poorly functioning kidneys treated surgically vs. conservatively after a trial of internal urinary diversion to assess the chance of function recovery. Study design: retrospective review of 17 consecutive patients with unilateral PUJO in kidneys with Differential Renal Function (DRF) <20% undergoing temporary internal urinary diversion between 2009 and 2021 at single tertiary center. DRF was reassessed after 1-3 months of diversion and subsequent management was conservative or surgical (pyeloplasty or nephrectomy) based on surgeon’s and family’s preferences without randomization. Results: After a trial of internal urinary diversion, 4/17 patients (23%) showed a DRF increase ≥5% (9%-12%), up to a maximum DRF of 28%, 3 underwent pyeloplasty, while 1 was managed conservatively. The remaining 13 patients showed no differential renal function improvement after diversion, and 7 were managed expectantly while6 surgically (4 pyeloplasty, 2 nephrectomy). Overall, nine patients (53%) were managed surgically and 8 (47%) expectantly After a median (range) follow-up of 3.1 (0.3-7.9) years, no significant difference was observed between groups regarding symptoms (p=0.205), need for further surgery (p=1.000), and renal function (p=1.000). Discussion: Although fraught with the limitation of a small sample size, this is the first study reporting on the conservative management of this controversial group of patients. Conclusions: In present pediatric series of pyelo-ureteral Junction obstruction in poorly functioning kidneys with differential renal function <20%, function recovery after a trial of internal urinary diversion was quite exceptional, and no difference was observed in outcome between patients managed surgically and conservatively after stent removal.